Prospects for expanding the range of medicinal products based on velvet antlers - Khvorost, O. P.; Rudnyk, A. M.; Fedchenkova, Yu. A.; Skrebtsova, K. S.; Simonian, L. S.; Volkova, A. V.; Хворост, О. П.; Рудник, Анна Михайлівна; Федченкова, Ю. А.; Скребцова, К. С.; Сімонян, Л. С.; Волкова, А. В. (My University, 2020)
Aim. To determine the feasibility of creating new medicines from antler BAS by analyzing the range of the medicinal raw material, medicines, dietary supplements and other pharmacy products based on antlers in the pharmaceutical market of Ukraine. Materials and methods. The analysis of the range of medicines and dietary supplements was carried out based on data from the State Register of Medicines of Ukraine, the electronic resource Compendium.online, according to the ATC classification system as of January – February, 2025. Information on retail prices was obtained from the online service www.tabletki.ua and available online marketplaces. The methods of information and bibliographic search, systematization, analysis and generalization, comparative, marketing, content analysis and graphic were used in the work. Results. Based on the results of the study, it was determined that only one product name with the antler raw material was registered as a medicinal product – “Pantocrin”, liquid extract, 50 ml, manufactured by Ternopharm (Ukraine). Among the entire product range, the share of dietary supplements is almost 93 %. The main suppliers of these products are foreign manufacturers from China and the USA, which total share is 63.6 %, domestic manufacturers account for 25 % of the range. It has been found that the domestic pharmaceutical market contains the raw material of antlers (slices, powder), dry and liquid extracts, liquid dosage forms (tinctures, drops, elixirs), tablets, pills, capsules, creams, cream-balms, gels, sprays and teas. Мета – з’ясування доцільності створення нових лікарських засобів з БАР пантів шляхом аналізу асортименту лікарської сировини, лікарських засобів, дієтичних добавок та інших товарів аптечного асортименту на основі пантів на фармацевтичному ринку України. Матеріали та методи: аналіз асортименту лікарських засобів та дієтичних добавок здійснювали на основі даних Державного реєстру лікарських засобів України, електронного ресурсу Compendium.online, відповідно до класифікаційної системи АТХ, станом на січень–лютий 2025 р. Інформацію про роздрібні ціни отримували на онлайн-сервісі www.tabletki.ua та доступних онлайнмаркетплейсах. У роботі використовували методи інформаційного та бібліографічного пошуку, систематизації, аналізу та узагальнення, порівняльний, маркетинговий, контент-аналіз та графічний. Результати дослідження. За результатами дослідження визначено, що як лікарський засіб зареєстровано лише одне найменування товару із сировиною пантів – Пантокрин, екстракт рідкий 50 мл виробництва «Тернофарм» (Україна). З усього асортименту товарів частка дієтичних добавок становить майже 93 %. Основними постачальниками цих товарів є закордонні виробники з Китаю та США, сумарна частка яких складає 63,6 %, на частку вітчизняних виробників припадає 25 % асортименту. Установлено, що на вітчизняному фармацевтичному ринку присутня сировина пантів (слайси, порошок), сухі та рідкі екстракти, рідкі лікарські форми (настойки, краплі, еліксири), таблетки, пілюлі, капсули, креми, креми-бальзами, гелі, спреї та чаї.
Перспективи розширення асортименту лікарських засобів на основі пантів
Keywords: antlers; raw material; medicines; dietary supplements; assortment; pharmaceutical market; панти; сировина; лікарські засоби; дієтичні добавки; асортимент; фармацевтичний ринок